Burn Wound and Traumatic Inhalation due to Marapi Volcano Eruption - Deddy Saputra; Gusman, Arief; Melati Purnama Sari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background. Burns can be caused by various etiologies, including heat and chemicals from volcanic eruptions. Mount Marapi was a commonly visited hiking site prior to its eruption on December 3th 2023. Case Presentation. This case reports a 19 year old woman with severe full thickness burns, covering 40.5% of total body surface area (TBSA) with inhalation trauma caused by inhaled volcanic ash from the Mount Marapi's eruption. Airway assessment was done through bronchoscopy examination.While being treated in the burn unit, the patient's overall condition deteriorated, so the patient was moved to the intensive care unit (ICU). Severe burns usually can cause circulatory disruption and trigger systemic inflammatory responses. Meanwhile, inhalation injury and sepsis also contributes to a higher risk of death in burn patients. Burns with inhalation trauma require specific treatment procedures. Conclusion. This study summarizes the experience of treating victim of the Mount Marapi eruption and multidisciplinary approach to achieve optimal patient care.